Jerusalem of Lithuania : A Reader in Yiddish Cultural History - Frakes, Jerold C. (Book collections on Project MUSE., 2011)
This is a Yiddish reader for intermediate-level students. It contains historical readings that recreate the importance of Vilnius (Lithuania) in preserving Jewish theology and culture during the last five centuries.